3GPP Channel Model Emulation with Analysis of MIMO-LTE Performances in Reverberation Chamber. (5th April 2012) - Arsalane, Nabil; Mouhamadou, Moctar; Decroze, Cyril; Carsenat, David; Garcia-Fernandez, Miguel Angel; Monedière, Thierry
Abstract : Emulation methodology of multiple clusters channels for evaluating wireless communication devices over-the-air (OTA) performance is investigated. This methodology has been used along with the implementation of the SIMO LTE standard. It consists of evaluating effective diversity gain (EDG) level of SIMO LTE-OFDM system for different channel models according to the received power by establishing an active link between the transmitter and the receiver. The measurement process is set up in a Reverberation Chamber (RC). The obtained results are compared to the reference case of single input-single output (SISO) in order to evaluate the real improvement attained by the implemented system.